REPRESENTASI GAYA HIDUP KAUM URBAN DALAM IKLAN ROKOK A MILD VERSI BUKAN MAIN - Abd. Rauf; Ringgo Eldapi Yozani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Advertising is a factor that supports the success of selling a cigarette brand. Advertising can be a representation of social reality. For example, The "Bukan Main" version of A Mild's cigarette advertisement which tells about the lifestyle of the urban community with satire lyrics sung by Iga Massardi, vocalist of the band Bara Suara. This version used a theme to satirize consumers' bad habits. Therefore, the purpose of this study was to find out how the representation of urban lifestyles in the "Bukan Main" version of the A Mild cigarette advertisement is.         This study uses qualitative research methods with semiotic analysis of Roland Barthes. The subjects of this research are scenes that describe how the lifestyle of the urbanites in the “Bukan Main” version of the A Mild cigarette advertisement and the objects in this study are audio and visuals related to the urban lifestyle in the “Bukan Main” version of the A Mild cigarette advertisement.         Based on the results of research data analysis using Roland Barthes' semiotic theory and urban lifestyles, the representation of urban lifestyles in the "Bukan Main" version of A Mild cigarette advertisements can be concluded as follows: (1) The denotative meaning expressed in the “Bukan Main" version of A Mild's cigarette advertisement is a social criticism of unfavorable behaviors carried out by people living in urban areas through singing with sarcasm lyrics, such as jumping in line, hanging out and taking photos of food to be uploaded on the internet, postings on social media do not correspond to reality, and rely on smartphone; (2) The connotative meaning of the "Bukan Main" version of A Mild's cigarette advertising message is about the lifestyle of the urban community that has been criticized. An urban setting that has progress and modernization of infrastructure is connoted as the mindset of an urban community that is also advanced. Hanging out and taking photos of food connotes social status, actions in cyberspace are not in accordance with reality connotes self-image, jumping in line is connoted as high life competition, and in scene 5 it connotes that urban communities are dependent on technology; (3) The myth of the message displayed by A Mild's version of “Not Main” is a myth about the opinion of urban communities that urban people have a more advanced way of thinking than rural communities, are familiar with technology, exist and are individualistic.Keywords:  Representation, Semiotic, Advertisement, Cigarette, Urban People